2019
DOI: 10.1111/zph.12666
|View full text |Cite
|
Sign up to set email alerts
|

Spotted fever group rickettsiae canine serosurveillance near the US–Mexico border in California

Abstract: Background: Dogs are vulnerable to pathogens transmitted by brown dog ticks. An epidemic of Rocky Mountain spotted fever (RMSF) is underway in Mexicali, aMexican city bordering California affecting people and dogs; several human cases have been reported in California residents who travelled to Mexico. To evaluate risks of RMSF, we conducted seroprevalence surveys in Imperial County in 2016 and 2017 using dogs as sentinels.Methods: Blood was collected from 752 dogs and was tested for antibodies against R. ricke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Although our findings suggest that dog reproductive performance and turnover are important factors affecting the transmission of RMSF in Mexicali, it is probable that the epidemiological dynamics of the diseases are also influenced by other indirect and direct, multifactorial factors including socioeconomic, biological, and environmental factors at different temporal and spatial scales [13,18,21,46]. For instance, although this study focused on owned freeroaming dogs, dogs of unknown ownership were often observed by study participants, and https://doi.org/10.1371/journal.pone.0233567.g005…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…Although our findings suggest that dog reproductive performance and turnover are important factors affecting the transmission of RMSF in Mexicali, it is probable that the epidemiological dynamics of the diseases are also influenced by other indirect and direct, multifactorial factors including socioeconomic, biological, and environmental factors at different temporal and spatial scales [13,18,21,46]. For instance, although this study focused on owned freeroaming dogs, dogs of unknown ownership were often observed by study participants, and https://doi.org/10.1371/journal.pone.0233567.g005…”
Section: Plos Onementioning
confidence: 77%
“…Since 2008, an outbreak of RMSF is ongoing in Mexicali, a city of 700,000 people immediately south of the border with the US, affecting at least 1000 people and countless dogs, with a high human mortality rate of approximately 40% [16]. In Mexico, the vector is a distinct tropical lineage of brown dog tick, in contrast with epidemics in Arizona associated with the temperate lineage [17]; increased warming and drying associated with climate change may permit the tropical lineage ticks to expand northward, with evidence that canine exposure is increased directly north of the US/Mexico border [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies aimed at identifying the tick vector, potential animal reservoirs, and prevalence are ongoing. These 3 canine rickettsioses cases underscore the value of dogs as sentinels for emerging tickborne pathogens (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in Mexico, the seroprevalence of TBBPs detected in both ticks and animals was common [ 19 , 20 , 21 , 22 , 23 ], and surveys on the diversity of ticks were carried out [ 21 , 24 ]. However, this research represents the first systematic study performed at the Mexico–US border, where the co-infestation with R. sanguineus s. l. and O. megnini , naturally parasitizing domestic dogs and FRD, the prevalence of TBBPs, and the association among the infestation with R. sanguineus s. l. males and E. canis infection in dogs were identified.…”
Section: Discussionmentioning
confidence: 99%